Wielka inicjacja. O znaczeniu podróży do Francji w roku 1890 dla poglądów i postawy artystycznej Stanisława Wyspiańskiego - Bałus, Wojciech (Przestrzenie Teorii, 2007)
Stanisław Wyspianski's journey to France, which he made thanks to Tadeusz Stryjeński in 1890, influenced the artistic development of the young painter. In his letters, written during his journey and addressed to T. Stryjeński, and in his poetic notes to Lucjan Rydel, Wyspiański keeps a record of his impressions and conceptualises his own artistic views, which are confronted on the spot with art and architecture which he saw during his journey (among others, Puvis de Chavannes, Gothic cathedrals, the Louvre, Sainte-Chapelle).